Réponses détaillées :
Programme 1 :
x = 4
A = (x+3)*(x+2)-6
A = (4+3)*(4+2)-6
A = 7*6-6
A = 42-6
A = 36
-----------------------
x = -1
B = (x+3)*(x+2)-6
B = (-1+3)*(-1+2)-6
B = 2*1-6
B = 2-6
B = -4
Programme 2 :
x = 4
C = x² + 5*x
C = 4² + 5*4
C = 16 + 5*4
C = 16 + 20
C = 36
-----------------------
x = -1
D = x² + 5*x
D = -1² + 5*(-1)
D = 1 + 5*(-1)
D = 1 - 5
D = -4
RAPPEL :
(-) * (-) = (+)
(+) * (+) = (+)
(-) * (+) = (-)
RAPPEL n°2 : ORDRE DE PRIORITÉ : (dans l'ordre)
PS : Je t'ai mis des rappels au cas où :)